Chapter 22 Social Credit System and Privacy - Chen, Mo (Taylor & Francis, 2023)
The Chinese Social Credit System (SCS), the first nationwide digitally implemented social rating system, aims to enhance trustworthiness within Chinese society and serves as a critical example of digital transformation of society. It is further designed to improve moral behavior, financial reliability, and social control. The implementation of the SCS is based on a large scale of personal information collection, processing, evaluation, and disclosure, which raises serious privacy concerns. This chapter briefly introduces the SCS before delving into the privacy issues raised by the SCS's two branches: the government-run SCS and the commercial branch. We discuss three major privacy concerns. First, personal information disclosed via the SCS blacklists and redlists is a considerable challenge to privacy and even security. Second, the SCS framework further facilitates personal data flows from the private sector to the government. Third, although the Chinese legal environment for privacy protection is evolving, enforcement is lacking. Finally, we shed light on using SCS data for research.